FUNGSI HUKUM DALAM PEMBANGUNAN EKONOMI - Kresna Puspita Santi, Dewa Ayu Made; Parwata, I Gusti Ngurah (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 06, Juli 2013, 2013)
The title of this writing is The Function of Law in Economic Development thatalso becomes the main problem to be discussed. The writing is based on a research ofnormatif using primary and secondary materials. The problem is analyzed throughstatue and analytical conceptual approach.Based on the library research, it can be concluded that the function and therole of law is very strategic in economic development. The law realized in theregulations functions to guide, provide references, and become tools for reaching thegoal of the development being desired.
Keywords: Function of Law, Economic Development